An Emphasis on the Critical Roles of Academic Simplified Material and its Influences on Learners' Boredom in Online Instruction, Attitudes to Electronic Learning, Self-regulated Online Learning, and Language Achievement - Goodarz Shakibaei; Arash Hashemifardni; Maryam Amini (Journal of Modern Research in English Language Studies)
As education is remodeled to online solutions, instructors and students must adapt their teaching and learning materials. This study inspected how Iranian EFL learners' attitudes toward electronic learning, selfregulated online learning (OL), boredom, and English language achievement were affected by academic simplified materials. To do this, 70 intermediate volunteers were chosen using a quasi-experimental design based on a convenience sampling method. Two experimental groups (EGs) (one for simplified texts and the other for authentic texts) were selected. Next, both groups took the pretests on general English, boredom, and self-regulated learning (SRL). Then, one group was trained in 12 simplified reading texts through online instruction, while the other group was trained in 12 authentic texts without using online teaching. After the treatment sessions, both groups took the general English, boredom, and SRL post-tests. Finally, a questionnaire was administered to the participants of the simplified group to explore their general viewpoints about applying simplification and simplified materials. The analyses showed substantial differences amongst the posttests of the groups in favor of the simplified group. The outcomes suggested that the simplified group considerably outflanked the authentic group on the posttests. Besides, the analyses showed that Iranian EFL learners had positive attitudes toward teaching simplified texts via online instruction.